Financial Development, Default Rates and Credit Spreads. Issue 626 (10th September 2019) - Peri, Alessandro; Rachedi, Omar
Abstract: US corporate default rates increased dramatically from an annual average of 0.32% between 1950 and 1984 up to 1.65% since 1985. Meanwhile, credit spreads rose by just 6 basis points. We argue that financial development—intended as an exogenous reduction in the fixed cost of borrowing—accounts for this evidence. In a heterogeneous firm model financial development boosts both default rates and firms' expected recovery rates. These two effects offset each other, muting the change in the credit spreads. The model explains 63% of the rise in default rates and predicts a 6 basis point drop in the credit spreads.